Penggunaan Alat Peraga Jarimatika sebagai Media untuk Meningkatkan Hasil Belajar Siswa pada Materi KPK dan FPB di Kelas V SD Kristen Benjina - Talupun, Yohalena; Takaria, J.; Ishabu, La Suha (Kamboti Journal of Education Research and Development, 2022)
This study aims to improve the learning outcomes of fourth graders at SD Kristen Benjina on the KPK and FPB materials. The method of this research is classroom action research that uses a Jarimatika teaching aid. Data collection techniques used are observation, interviews, tests and documentation. The results showed that the use of Jarimatika media could improve student learning outcomes in KPK and FPB learning for fourth grade students at SD Kristen Benjina. Student learning outcomes have met the researchers' success indicators, namely 70% on each indicator of learning outcomes. the percentage of student learning outcomes in the pre-cycle is 30%. In the first cycle of 45% %, and in the second cycle it reached 85%. Based on the results of data analysis, the use of Jarimatika teaching aids in the KPK and FPB materials can improve the learning outcomes of fourth graders at SD Kristen Benjina